(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Digital health technologies are transforming medication management, patient safety, and healthcare accessibility. Rx Medicare is a blockchain-based digital platform designed to provide secure medication management and integrated patient healthcare records while supporting interoperability with existing healthcare systems. The platform uses blockchain technology to ensure tamper-resistant storage of prescriptions and medical records, enhancing data security, privacy, and data integrity. A unique patient identification system linked with the Aadhaar number enables authorized healthcare providers to securely access patient medication histories across hospitals and pharmacies, ensuring continuity of care while minimizing duplication of medical records.The application offers multi-platform medication reminders, including SMS notifications for non-smartphone users, to improve medication adherence and reduce missed doses. Patient records are maintained in a structured chronological order, allowing healthcare professionals to efficiently review medication history, diagnoses, laboratory reports, allergies, and previous treatments. The platform also securely stores mediclaim and health insurance information to facilitate faster claim verification and processing. Additionally, an integrated pharmacy inventory management module monitors medicine stock levels, expiry dates, and availability, helping reduce medication shortages, prevent wastage, and improve inventory efficiency.By enabling secure access to health records across different healthcare settings and geographical locations, Rx Medicare supports informed clinical decision-making, coordinated patient care, and improved communication among healthcare providers. The proposed system aims to enhance medication adherence, strengthen healthcare data security, optimize pharmacy inventory management, improve patient safety, and increase healthcare efficiency. This project demonstrates the potential of blockchain-enabled digital health technologies to modernize pharmacy practice, promote digital healthcare transformation, and improve overall patient outcomes.